Identifikasi Dan Analisis Potensi Desa Di Daerah Kantong Tki Dalam Rangka Pelaksanaan Program Desmigratif - Yeni Nuraeni (Jurnal Ketenagakerjaan, 2017)
Desmigrative program is one of the strategies launched by the government to overcome the problems of migrant workers in the informal sector which shows the many problems faced by TKI with minimal protection. To ensure that desmigrative programs are on target, it is necessary to identify the target villages. The purpose of the identification activity is to know the potential of the village so that it can be concluded the urgency, thesupporting factors, the inhibiting factors or what actions need to be done on the target villages so as to ensure that the desmigrative program can be implemented and achieve its objectives. The study was conducted in 120 villages including the pockets of migrant workers (the number of relatively large TKI) scattered in 10 Provinces. This research includes descriptive research with the use of both quantitative and qualitative data. From theresults of the research can be concluded to be able to carry out desmigrative program in the target villages need to be considered the urgency, inhibiting, supporting factors as the basis for performing the most appropriate action so that the Desmigrative Program can achieve its goal maximally in order to increase the welfare of active migrant workers and former migrant workers and their families.